Ovarian cancer familial relative risks by tumour subtypes and by known ovarian cancer genetic susceptibility variants. Issue 2 (25th November 2013) - Jervis, Sarah; Song, Honglin; Lee, Andrew; Dicks, Ed; Tyrer, Jonathan; Harrington, Patricia; Easton, Douglas F; Jacobs, Ian J; Pharoah, Paul P D; Antoniou, Antonis C
Abstract : Background: Family history is one of the most important risk factors for epithelial ovarian cancer (EOC). Little is known, however, on how EOC familial relative risks (FRRs) vary by factors such as tumour subtype or the combined effects of common EOC susceptibility alleles. In addition, no data currently exist on the FRRs associated with EOC after exclusion of BRCA1 or BRCA2 mutation carriers. Methods: EOC FRRs were computed from observed EOCs in relatives of 1548 patients with EOC recruited between 1999 and 2010 from a population-based cohort study with known BRCA1 and BRCA2 mutation status and tumour subtype, compared with the number expected in the general population. Results: The EOC FRR to all first-degree relatives was estimated to be 2.96 (95% CI 2.35 to 3.72) but there was no evidence of difference in the FRRs for mothers, sisters and daughters. There was significant evidence that the FRR for relatives of patients with EOC diagnosed under age 50 years is higher than that for older patients (4.72 (95% CI 3.21 to 6.95) and 2.53 (95% CI 1.91 to 3.35), p-diff=0.0052) and a suggestion that the FRR in relatives of patients with serous disease is higher than that for non-serous tumours (3.64 (95% CI 2.72 to 4.87) and 2.25 (95% CI 1.56 to 3.26), p-diff=0.0023). The FRR to relatives of cases without a deleterious mutation in BRCA1 or BRCA2 was estimated to be over twice that of the general population (2.24 (95% CI 1.71 to 2.94)). BRCA1 and BRCA2 mutations were estimated to account for about 24% of the EOC FRR to first-degree relatives. FRRs were found to increase with increasing polygenic risk score of the index patient, although the trend was not significant. Conclusions: These estimates could be useful in the counselling of relatives of patients with ovarian cancer.